Selection of Control Device Parameters for Electric Drive with Pulse Transducer - O. F. Opeyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper reveals the conditions which are to be met by parameters of micro-controller accuracy and speed (a number of discharges in data word, clock frequency of a timer) and number of pulses per transducer revolution that ensure the required accuracy of the system to control position and speed. In this case measuring time is taken into account which is permissible in accordance with the conditions of stability margin preservation